2019
DOI: 10.1091/mbc.e19-01-0046
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial carrier protein overloading and misfolding induce aggresomes and proteostatic adaptations in the cytosol

Abstract: Previous studies in yeast showed that mitochondrial stressors not directly targeting the protein import machinery can cause mitochondrial precursor overaccumulation stress (mPOS) in the cytosol independent of bioenergetics. Here, we demonstrate mPOS and stress responses in human cells. We show that overloading of mitochondrial membrane carrier, but not matrix proteins, is sufficient to induce cytosolic aggresomes and apoptosis. The aggresomes appear to triage unimported mitochondrial proteins. Interestingly, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…Moreover, stably overexpressing SFXN1 in SFXN1 KO partially improved CIII function ( Figures S4D and S4E ). We speculate that reintroducing SFXN1 at a physiological level may provide a better rescue, as overexpression of MCs has been shown to induce an aggregation-based, cytosolic stress response ( Liu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, stably overexpressing SFXN1 in SFXN1 KO partially improved CIII function ( Figures S4D and S4E ). We speculate that reintroducing SFXN1 at a physiological level may provide a better rescue, as overexpression of MCs has been shown to induce an aggregation-based, cytosolic stress response ( Liu et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Presumably owing to their hydrophobic nature, carrier proteins were reported in the past as being a severe burden for cytosolic proteostasis when their mitochondrial import is impaired (Hoshino, Wang et al, 2019, Liu, Wang et al, 2019, Piard, Umanah et al, 2018, Wang & Chen, 2015). We employed an established assay of PROTEOSTAT staining (Pihlasalo, Kirjavainen et al, 2011) to monitor the formation of misfolded proteins in yeast cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, major clients of the Mia40 pathway are the small Tim proteins, essential components for the import of inner membrane carriers (Koehler, Jarosch et al, 1998, Luciano, Vial et al, 2001). Carriers are very abundant hydrophobic proteins and it is well documented that misfolded or non-imported carriers pose a major threat to cytosolic proteostasis (Hoshino et al, 2019, Liu et al, 2019, Vartiainen, Chen et al, 2014, Wang & Chen, 2015). Consistent with this idea, a previous genome-wide overexpression screen for suppressors of polyQ toxicity identified a large number of components of the carrier import pathway, including Erv1, Tim9, Tim10, Tim12, and Tim22 (Mason et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies showed that overloading of mitochondria with carrier proteins leads to the accumulation of unimported mitochondrial proteins in the cytosol, followed by proteostatic stress (or mPOS) and cell death 5 . However, it is unknown whether mPOS can occur in vivo and whether it causes pathology.…”
Section: Resultsmentioning
confidence: 99%